Distribution of blue-green algae in soils of Chittagong University campus and their nitrogen fixing capacity - Gafur, MA; Parvin, Soltana (Bangladesh Journal of Botany, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Occurrence of blue-green algae in plain land, pond side, hilly area and dry rice field soils of Chittagong University Campus and N2 fixation of some of them have been studied. Twenty four species under 20 genera were identified and their number varied from 0.11Ã104/g to 2.8Ã104/g soil. Anabaena oryzae, Calothrix sp., Cylindrospermum majus and Hapalosiphon hibernicus and Nostoc spongiaeforme were selected for their nitrogen fixing potential. Maximum amount of total nitrogen was recorded in Nostoc spongiaeforme followed by Hapalosiphon hibernicus, Cylindrospermum majus, Anabaena oryzae and Calothrix sp. after 30 days growth in batch cultures. Â  Key words: BGA, Distribution, Nitrogen fixation doi:10.3329/bjb.v37i1.1563 Bangladesh J. Bot. 37(1): 49-53, 2008 (June)